2014
DOI: 10.2478/sjph-2014-0001
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of sports activity with stress and satisfaction with life among adult Slovenians

Abstract: IzvlečekIzhodišča: Namen raziskave je bil ugotoviti povezanost med športno dejavnostjo (ŠD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The results of Imayama on postmenopausal women showed the same (37). Physical activity has several positive effects on similar outcomes, such as lowering the stress and improving satisfaction with life (38). Adequate physical activity has been shown to be a positive predictor of HRQoL for middle-aged and older people in several other studies (31,(37)(38)(39), specifically pointing out that not only aerobic activity is important, but also building body strength and flexibility (39)(40)(41).…”
Section: Discussionsupporting
confidence: 54%
“…The results of Imayama on postmenopausal women showed the same (37). Physical activity has several positive effects on similar outcomes, such as lowering the stress and improving satisfaction with life (38). Adequate physical activity has been shown to be a positive predictor of HRQoL for middle-aged and older people in several other studies (31,(37)(38)(39), specifically pointing out that not only aerobic activity is important, but also building body strength and flexibility (39)(40)(41).…”
Section: Discussionsupporting
confidence: 54%
“…As expected, the perceived physical work demand was positively, and the perceived mental work demand negatively related to physical activity in the work domain, whilst the perceived work demand was the only significant predictor of the total physical activity. Leisure-time physical activity was not related to work characteristics, although previous studies have shown that stressful work accompanied with high psychological demands increases the likelihood of physical inactivity in the leisure-time [33,34]. It has even been suggested that the leisure-time physical activity may serve as a protective factor against work strain and work demands among young adults [35].…”
Section: Correlates Of Physical Activitymentioning
confidence: 78%
“…Physical activity has several positive effects on similar outcomes, such as lowering the stress and improving satisfaction with life ( 38 ). Adequate physical activity has been shown to be a positive predictor of HRQoL for middle-aged and older people in several other studies ( 31 , 37 , 38 , 39 ), specifically pointing out that not only aerobic activity is important, but also building body strength and flexibility ( 39 , 40 , 41 ). We described the level of physical activity only by aerobic exercise, which is also the most advised in patient counselling.…”
Section: Discussionmentioning
confidence: 99%